Activation of G Protein-Coupled Estrogen Receptor (GPER) Negatively Modulates Cardiac Excitation–Contraction Coupling (ECC) through the PI3K/NOS/NO Pathway - Diaz Zegarra, Leandro Agustin (2024)
The G-protein-coupled estrogen receptor (GPER) has been described to exert several cardioprotective effects. However, the exact mechanism involved in cardiac protection remains unclear. The aim of this study is to investigate the role of GPER activation on excitation–contraction coupling (ECC) and the possibility that such effect participates in cardioprotection. The cardiac myocytes of male Wistar rats were isolated with a digestive buffer and loaded with Fura-2-AM for the measurement of intracellular calcium transient (CaT). Sarcomere shortening (SS) and L-type calcium current (ICaL) were also registered. The confocal technique was used to measure nitric oxide (NO) production in cells loaded with DAF-FM-diacetate. Cardiac myocytes exposed to 17-β-estradiol (E2, 10 nM) or G-1 (1 μM) for fifteen minutes decreased CaT, SS, and ICaL. These effects were prevented using G-36 (antagonist of GPER, 1 μM), L-Name (NO synthase -NOS- inhibitor, 100 nM), or wortmannin (phosphoinositide-3-kinase -PI3K- inhibitor, 100 nM). Moreover, G1 increased NO production, and this effect was abolished in the presence of wortmannin. We concluded that the selective activation of GPER with E2 or G1 in the isolated cardiac myocytes of male rats induced a negative inotropic effect due to the reduction in ICaL and the decrease in CaT. Finally, the pathway that we proposed to be implicated in these effects is PI3K-NOS-NO.